The Return of Giuseppe Castiglione: Lang Shining (1688–1766) Comes Back to Europe - Dubrovskaya, Dinara V. (Actual Problems of Theory and History of Art, 2021)
Recognized leader of European masters at the court of the Manchu rulers of China in the 18th century, Italian Jesuit artist Giuseppe Castiglione gained wide popularity among art critics and connoisseurs of Chinese art only in the post-war period, which is both natural and paradoxical, because the young Baroque master who had departed for China as a Jesuit lay brother disappeared from European art history, of course, without getting lost in the archives of the order. The article aims to bring together several vectors, where the most fundamental component of the problem is the actual work of the artist, striving to find out who knew that the author of, e.g., the drawings brought to France for a series of engravings on the ‘Conquest of Xi-yu’ was Castiglione, and, finally, when the non-Chinese art-world first met Lan Shining’s paintings and realized the identity of Lan Shining as Castiglione? The author demonstrates that this identification took place in China earlier than in Europe, based on information from the court archives; besides Chinese court art has never forgotten the fact that Castiglione and his associates introduced European trends, initiated and supported by the Manchu emperors. Thus, the article briefly traces the circumstances of the return of Giuseppe Castiglione’s name and legacy to European art history, starting with the archives of the Jesuit Order, through the Peking Gogong palace exhibitions and catalogues and, finally, to the pioneering work of George Loehr, which we can be considered the beginning of a full-fledged study of the Italo-Chinese master’s art in the 20th–21st centuries.